Promoción de productos de lona en medios digitales de la empresa “Mochilas Ambato” - Diego Bladimir, Chuncho Torres (2025)
This research addresses the need to strengthen the digital presence of the company "Mochilas Ambato", dedicated to the manufacturing and marketing of canvas backpacks, in light of increasing competition and changes in consumer behavior. The identified problem was the limited promotion of its products through digital channels, which has restricted its reach and the consolidation of its positioning in the local market. The general objective was to design and evaluate digital promotion strategies aimed at increasing brand visibility, improving interaction on digital platforms, and establishing a better relationship with the target audience. To this end, a mixed-method approach was employed in the methodology, with the application of structured surveys to consumers and the analysis of social media performance of competing companies. This methodology integrated quantitative and qualitative analysis of consumer preferences and the effectiveness of digital publications. The results showed that the target audience primarily uses social networks, especially Facebook, Instagram, and TikTok, to interact with brands. It was concluded that the appropriation of the visual value of products and consistency in publications, combined with the implementation of differentiated strategies for each digital channel, facilitate positioning and consumer loyalty. Finally, it is recommended to consolidate a coherent brand identity and maintain continuous digital marketing planning to ensure the company's sustainable growth.